2023
DOI: 10.1186/s13690-023-01056-9
|View full text |Cite
|
Sign up to set email alerts
|

Health and social needs of older adults in slum communities in Ghana: a phenomenological approach used in 2021

Abstract: Slum-dwellers lack several essential amenities (such as water, sanitation, and electricity) which make them more vulnerable than non-slum dwellers. As there is limited to no access to health and social care services in slums, the slum environment is expected to be an even more dangerous environment for older adults, negatively impacting their quality of life (QoL). To provide an overview of the perceived (unmet) health and social care needs and how it affects the QoL, this study aims to explore the self-percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The study showed that limited access to health and social care services in slums negatively impacts the quality of life of older adults. The study also revealed that social support from family members and friends facilitated adherence to self-care practices and medical consultations [ 27 ]. Another study conducted in 2022 explored the views of health professionals on the access to and use of health and social care services by slum-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that limited access to health and social care services in slums negatively impacts the quality of life of older adults. The study also revealed that social support from family members and friends facilitated adherence to self-care practices and medical consultations [ 27 ]. Another study conducted in 2022 explored the views of health professionals on the access to and use of health and social care services by slum-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy was measured using the 10-item General Self-Efficacy Scale [18], which assesses the perceived ability to cope with difficult demands in life on a 4-point Likert scale. The total score ranges from 10 to 40 points and is categorized as low (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), moderate (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), or high (31-40).…”
Section: Data Collection Tools and Techniquesmentioning
confidence: 99%